The second world war archives in France, from history to one's own history (Tempo e Argumento, 2013)
The public opening of the archives of the Second World War in the 1990s was a remarkable and sometimes conflicted episode in the recent history of archives in France. The period was marked, in effect, by a series of heated and sometimes controversial debates on the juridical conditions for the access to these documents. Here we return to these difficult years, striving to decipher what they could have meant in terms of the relationship between reader and archive documents. Behind an obvious need for history and a problematic social and collective memory that could not be denied, hides a very profound transformation of the logic of use of archive documents.
Keywords: archive; memory; archives - history; Second World War; jews